PENGARUH PENGEMBANGAN PRODUK DAN PROMOSI TERHADAP VOLUME PENJUALAN PRODUK GARAM REFINA (Studi Kasus Pada Pt Unichem Candi Indonesia) - Ambia, Muh Fachry; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aimed to determine the effect simultaneously and partially Product Development (X1) and Promotion (X2) on Sales Volume (Y). The sampling technique used is saturated samples and obtained a sample of 50 respondents. The analysis technique used is multiple regression analysis, F test and t test. Based on the results of the analysis indicate that the development and promotion of products simultaneously significant effect on the sales volume of PT. Unichem Candi Indonesia. Between these two variables, variables that have a dominant influence on the sales volume is variable product development. Based on this analysis, advice that can be given that the company carries out product development in order to continue to increase sales volume. In doing product development company should undertake new innovations and follow changes shape desired by consumers conducted by competitors. Once the product development is done should the company do in order to inform the development of promotional products to the public. Keywords: Product Development, Promotion, Sales Volume